2001
DOI: 10.1117/1.1390299
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric turbulence modulation transfer function for infrared target acquisition modeling

Abstract: A new direction for the US Army Night Vision and Electronic Sensors Directorate is the development of ultra-narrow field of view (UNFOV) infrared target acquisition (TA) systems. Frequently, the performance of these systems is limited by atmospheric turbulence in the imaging path. It is desirable to include the effects of atmospheric turbulence blur in infrared TA models. The current TA models are currently linear shift invariant (LSI) systems with component modulation transfer functions (MTFs). The use of add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 10 publications
0
17
0
Order By: Relevance
“…The main consideration is turbulence MTF and aerosol MTF. For space optical remote sensing applications, the turbulent MTF in the far field and short exposure condition can refer to literature [9,10]. Aerosol impact on image comes mainly from low altitude atmosphere part.…”
Section: Atmospherementioning
confidence: 99%
“…The main consideration is turbulence MTF and aerosol MTF. For space optical remote sensing applications, the turbulent MTF in the far field and short exposure condition can refer to literature [9,10]. Aerosol impact on image comes mainly from low altitude atmosphere part.…”
Section: Atmospherementioning
confidence: 99%
“…A laser beam propagating through unstable random atmosphere experiences phase and amplitude variations due to turbulence disturbances leading to such effects as beam wander, beam spreading, and intensity fluctuations better known as scintillations [6,8,10]. This turbulence is caused by refractive index inhomogeneities along the propagation path and it has significant degrading impact on the performance of free-space optical (FSO) communication systems as well as on the quality of imaging systems described by the modulation transfer function (MTF) [11][12][13]. In addition factors like aerosol scattering, molecular absorption caused by snow, fog, and rain can also severely degrade the quality of imaging systems [9].…”
Section: Introductionmentioning
confidence: 99%
“…The standard theory for modeling atmospheric turbulence impacts in systems performance models [1][2][3] has been Fried's 4 short-exposure atmospheric modulation transfer function (MTF). Reanalysis of Fried's approach has shown that when diffraction influences on the phase structure function are included, 5 the tilt-phase (TP) correlation term is numerically evaluated, 6 and path-dependent turbulence strength variations are considered.…”
Section: Introductionmentioning
confidence: 99%